REKONSTRUKSI KOMPONEN DAN MODEL PENGEMBANGAN KURIKULUM PAI DALAM MENGHADAPI TANTANGAN MODERNITAS - Burhan, Mohammad Nurul; Fajarwati, Anita; Maimun; Agus Moh Sholahuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid flow of modernity, marked by technological disruption, shifting moral values, and secularism in education, poses a crucial challenge to the existence of Islamic Religious Education (PAI) in Indonesia. The PAI curriculum is often considered too cognitive-textually oriented and insufficiently adaptive to dynamic social realities. This research aims to reconstruct the main components of the PAI curriculum and evaluate relevant development models to address the challenges of the times. This research uses a qualitative approach using library research. Data are analyzed descriptively and analytically using hermeneutical techniques to examine classical and contemporary curriculum concepts. The reconstruction focuses on four main components: (1) Objectives, which must transform from merely theological understanding to the formation of prophetic awareness and life skills; (2) Materials, which interconnectively integrate science and religion; (3) Methods, which adopt a digital-based, student-centered learning approach; and (4) Evaluation, which emphasizes authentic and moral aspects holistically. The study's findings indicate that the centralized (top-down) Islamic Religious Education (PAI) curriculum development model needs to shift toward a more participatory and grassroots-based model to simultaneously accommodate local and global needs. This reconstruction has resulted in a proposed